Autoconhecimento emocional do professor : a preocupação com a pessoa, antes do profissional - Almeida, Lucia Helena Diniz de (2019)
The scenario of the XXI century brings to the teaching new challenges, of several orders, demanding a search for the best formation of its professionals. Expectations are expressed for a development from processes rich in meaningful, critical and participatory experiences. Social-emotional skills appear as fundamental to the teachers and make them seek in the neurosciences subsidies for their professional practice, in the different dimensions: cognitive, affective or social. It is increasingly argued that emotions need to be considered in educational processes: the teachers need to be attentive not only to the emotions of the students, but also to their own emotions, because the behavior of the educator assumes an importance not always thought but which affects the student’s learning. Thus, this Dissertation aimed to understand the feelings and emotions of the teachers in the classroom, to discover their difficulties and to show that the training of the graduates still needs to be rethought with respect to the teacher and the emotional self-knowledge. The research was qualitative and had a questionnaire with open answers, made online, which allowed a greater privacy and opportunity of expression of feelings and emotions. Seven students, from different undergraduate degrees, at a University of Porto Alegre - RS participated in the study. The literature review was developed from authors such as Vygotski, Freire, Guerra, Relvas, Damásio, Herculano-Houzel, Nóvoa, Morin, Goleman and Tardif, who point to ideas for a new inspiration in the (trans) formation of teachers. The analyses of the educational situations are evidenced and interact producing important elements to the learning, in a significant way. To analyze them, categories were created to correspond to the objectives proposed: 1-the teacher with himself: difficulties and challenges, 2-the teacher with the student: discoveries and learning, 3-the teacher in front of the classroom: knowledge and affection. Then, it was necessary to create another category, a posteriori: 4-the teacher with emotional skills: critical and reflexive. At the end, it is important to educate for resilience, empathy and affection through the development of social-emotional skills, as essential for enhancing the self-knowledge of the teacher, resulting in a significant possibility in learning. Social-emotional skills can and do need to be developed in the classroom through interaction, sharing and reflection. The focus of the research is the teacher's emotional self-knowledge and, in this perspective, there is still much to investigate and produce, in order to better meet the demands in classrooms. It is in this focus that we must bring innovative ideas, to add in knowledge and multiply the opportunities to (re) signify learning with effective quality.